Programmable Wide‐Spectrum Complex Microcavity Laser Controlled by Liquid Crystal Elastomer Braking Mechanism - Hongyang Zhu; Bingquan Zhao; Zhen He; Junxin Wei; Chensha Li (Advanced Photonics Research)
Complex laser architectures employing disordered microcavities demonstrate unique advantages characterized by micro/nano‐scale cavity dimensions, facile integration capabilities, exceptional sensitivity to external field perturbations, and extensive parametric tunability. These distinctive features have catalyzed the emergence of innovative paradigms for intelligent multidimensional external field manipulation, particularly through strategic employment of advanced functional materials. This article presents a fiber‐based microcavity complex laser system featuring programmable deformation control through a multiaxis liquid crystal elastomer (LCE) actuator under photothermal excitation. The resultant deformed LCE film serves both as a controllable localized scattering medium in the formation of fiber‐based microcavity complex lasers and as an intelligent actuator actively involved in photon resonance, coupling, and transmission within fiber‐arrayed microcavities. This dual functionality facilitates the generation, regulation, and transmission of broadband spectrum lasers through coordinated multiphysics interactions. Spatially patterned optical excitation facilitates programmable two‐dimensional contraction/expansion control of the LCE matrix, inducing switchable resonance regimes (either independent resonance or mutually scattering) within the coupled cavity system. The resulting wavelength‐agile platform exhibits broad spectral adaptability across multiple photonic operation regimes. This innovative approach significantly expands the functional scope of LCE materials, establishing a sophisticated technological framework for multidimensional photonic control in next‐generation optoelectronic systems.